Pengaruh Penerapan Total Productive Maintenance Terhadap Kinerja Perusahaan Farmasi di Jawa Timur - Widiaswanti, Ernaning (Universitas Trunojoyo Madura, 2009)
Many companies increase its organizational capability through investing in such programs as Just In Time (JIT) and Total Quality Management (TQM). Thebenefit of these programs, however, seems always limited because of less reliab1e equipment. Many companies find Total Productive Maintenance (TPM) to add into the existed programs in order to have continued improvement. Pharmaceutical industry becomes one that uses TPM to maintain its reliabilityfrom the equipment used to suP.E...ort production process. The objective of research aims at examining and analyzing the effect of